Pengaruh Lubang Pada Kolom Akibat Gaya Aksial Tekan - Batubara, Samsuardi; Manik, Danastasia (Fakultas Teknik Universitas Katolik Santo Thomas, 2018)
This research aims to investigate the effect of hole in reinforced concrete on column capacity,Â particularly in carrying axial forces. Tests were performed by applying axial forces on two types ofÂ sample: with-hole and without-hole. The ultimate load obtained from both type of samples wasÂ compared to determine the effect of the hole in the concrete specimen. Four samples were made,Â namely: no-hole in sample; hole sized 1â€ (2.25% of sample gross weight); sized 1Â¼â€ (3.52%); sizedÂ 1Â½â€ (5.067%). The dimension of the sample is 15x15cm, and 150cm height. These four samples areÂ reinforced with 4D10 and shear reinforcement of Ï•6. Testing equipment used in this research is jackÂ hydraulic with capacity of 200 tons. Based on theoretical calculation, capacity degradation caused byÂ hole inside a column is not significant. However, our test results show that axial capacity of the columÂ is significantly affected by the given hole. Sample with 3.52% of sample gross weight suffered aÂ 20.76% degradation, and sample with 5.067% of sample gross weight suffered a 33.27% degradation.